Cashing in on resources, social and cultural capital: the role of local markets in the Great Southern district of Western Australia - Curry, George; Fold, Niels; Jones, Roy; Selwood, John (University of North Dakota, 2008)
This paper focuses on the role of local fairs and markets in building upon and exploiting the physical resources and social and cultural capital of Albany and Denmark, two towns in the Great Southern district of Western Australia. It builds on earlier work of the team that has examined some of the drivers of local change in the region (e.g. Selwood et al. 1996; Curry et al. 2001). That work shows how in the recent past the region has experienced several waves of innovative immigrants who have largely transformed the traditional forestry and agricultural economic base of the area with the introduction of new crops and a variety of services catering to a growing tourism industry and early retirees to the district. Partly in response to these changes and also influenced by more global trends in social values, such as organic farming and the increasing emphasis on sustainable local economies, Albany and Denmark, the two most important towns of the area, have recently established periodic local markets which are catering to both the local population and to the growing regional tourism market. As such, they support the thesis that 'creativity' is an important and necessary ingredient in the development of rural communities. The marshalling of this creativity is a manifestation of social and cultural capital at work.